Design and Control Sweets Production Line - Mohammed, Samaro; Abdullah, Kalbouneh (My University, 2018)
Efficiency, productivity and saving time are key factors of most engineering projects. Production lines in particular take these factors and maximize them to the fully. In the 1990s and early 2000s a revelation in food industry expanded throughout the world, making it one of the most successful investment in any country’s industry. This project is about a machine that is designed to stuff and form edible products. There are some steps to form the final shape, starting with encrusting and ending with stamping. The machine is to produce a maximum of 3600 piece per hour with a maximum volume of 71 cm3, but can be controlled to produce less than the maximum quantity, and it can produce several shapes of products. The report includes the design of the machine using Solidworks, calculations of the machine parts. And it includes the processes the piece going through.